Memberitakan Injil Kepada Suku DONS di Era Digital - Frengky Marpaung; Rogate T.A. Gultom; Ibelala Gea (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Missionary is a characteristic of God that must be present in His people, as a form of imitation of God who saved all ethnic groups through the work of Jesus Christ. However, many ethnic groups, including the DONS tribe in North Sumatra, have not been reached by the gospel of salvation even though they are geographically easy to reach. Currently, pioneers who reach the DONS tribe face various obstacles, both from within the DONS community and from the pioneers themselves. By recognizing these obstacles, it is hoped that they can find creative solutions and utilize digital technology as an effective means of spreading the gospel. Exploring the elements of DONS culture is also important to create an approach that is easy for them to understand. Although pioneers have tried to utilize the culture, improvements are still needed in creative ways to produce new strategies that are more effective in outreach. All of these efforts are made on the basis of God's love, so that DONS people can know Jesus as the Way, the Truth, and the Life, and receive the salvation that God has given through Christ.